PEMANFAATAN PEELING BERAS KETAN HITAM SEBAGAI PENCERAHAN KULIT WAJAH - Jamil, Chyndi; Rostamailis, Rostamailis; Rosalina, Linda (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This is an experimental reseach with non equivalent control group desaign. The object of research is students of Padang State Unuversity who has the same criteria (oily skin type). Sampling is used with purposive sampling technique done in 6 people. The data collected from research directly from the sample by filling out the research format that has been provided. The collected data was analyzed using t test.The results showed that treatment without the use of glutinous rice glutinous peels in the control group did not show significant results in changes in skin brightness level. In the experimental group showed significant results on the brightness indicator of facial skin showed the highest score on the 8th treatment with a score of 3.67 categorized brightly. Hypothesis accepted because t count> t table equal to 4,261> 1,880. After treatment with samples with oily skin categories, significant differences with levels of Î± = 0.05 for facial care in the control group and experimental group. It is recommended that respondents use continuously. Keywords: Peeling Glutinous Rice, Oily Skin Face.